Duopoly in Space - John M. Hartwick; Philip G. Hartwick (Queen's University, Department of Economics, 1970)
Hotelling's 1929 article concerning the behavior of duopolists in a spatial setting has had a lasting influence in economics and political science. With a simple model, he was able to elucide why "our cities become uneconomically large and business districts within them too concentrated"; and why "Methodist and Presbyterian churches are too much alike;cider is too homogenous." In this paper, we develop the constant non-zero elasticity of demand case which Hotelling referred to.
Keywords: 330